Bilayer Structure with Ultrahigh Energy/Power Density Using Hybrid Sol–Gel Dielectric and Charge‐Blocking Monolayer. Issue 19 (14th July 2015) - Kim, Yunsang; Kathaperumal, Mohanalingam; Chen, Vincent W.; Park, Yohan; Fuentes‐Hernandez, Canek; Pan, Ming‐Jen; Kippelen, Bernard; Perry, Joseph W.
<x xml:space="preserve">Abstract</x> A hybrid sol–gel dielectric bilayer structure yields a maximum energy density of 40 J cm−3 with a high extraction efficiency. The silica sol–gel dielectric is coated by an alkylphosphonic acid monolayer, as a charge‐blocking layer. The dense monolayer suppresses charge injection and electrical conduction, leading to high energy extraction efficiency, which exhibits nearly linear dielectric behavior suitable for high energy density applications.